Classical and Modern Techniques for Liquid Refractive Index Measurement: Working Principles, Performance Comparison, and Applications - Arlin Maya Sari; Maulina Tanjung (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
The refractive index is a key physicochemical property of liquids, essential for quality control, chemical analysis, biomedical diagnostics, and environmental monitoring. Advances in optical instrumentation have led to the development of refractive index measurement techniques, evolving from conventional prism-based refractometers to automated, high-sensitivity optical systems. Despite this progress, comprehensive comparisons between classical and modern refractometric techniques are limited. This review compares four widely used liquid refractive index measurement techniques: the Abbe refractometer, the Pulfrich refractometer, the digital refractometer, and interferometric methods, focusing on their principles, advantages, limitations, performance, and applications. A structured literature review was conducted to analyze studies on measurement principles, instrumentation, operational characteristics, and practical applications. The findings show that classical refractometers remain reliable for routine measurements due to their simplicity, robustness, and cost-effectiveness. Digital refractometers offer improved automation, repeatability, and efficiency, while interferometric methods provide superior sensitivity and spatial resolution for high-precision applications, though they require more complex instrumentation and data processing. The choice of technique should be based on measurement accuracy, sample characteristics, operational requirements, and intended application.